The Ambiguous Allure of Ashoka: Buddhist Kingship AS Precedent, Potentiality, and Pitfall for Covenantal Pluralism in Thailand - Larsson, Tomas (The review of faith & international affairs, 2021)
In the course of the 20th century, Thai political elites fashioned a religiopolitical settlement that has a great deal in common with covenantal pluralism. They did so, furthermore, by rediscovering a historic precedent in the Indian emperor Ashoka, and reinterpreting the image of this paragon of Buddhist kingship so as to emphasize theological humility and a benevolent embrace of religious pluralism. Since the fall of the absolute monarchy in 1932, this Ashokan ideal has been reflected in the Buddhist Thai king’s constitutionally defined role as upholder of religions—in the plural. However, recent developments in Thailand highlight the difficulties associated with sustaining a tolerant and robustly pluralistic policy regime over time, and the inescapable normative trade-offs that this involves.